EUROPE AND SERBIAN FEUDALISM - END OF THE 14th CENTURY AND EARLY 15th CENTURY - RELEVANT ASPECTS - Staretu, Stefan (European Scientific Journal, ESJ, 2015)
Serbian feudalism goes through a strong expansion process in the 14th century. This direction was shaped by Ştefan Uros the First, who was already part of a family considered so important in Europe that he could marry Helen of Anjou, which shows the prestige of the power, origin and holiness of the Nemanide dynasty in Europe. On the other hand, Western feudalism was exhausted by the new bourgeoisie, and this area was a good place of enthusiasm for Westerners in search for their roots and warlike mentality. The Vidovdan in Sigismund's time animated all the medieval chivalry, and this enthusiasm was manifested by founding the Order of the Dragon. Sigismund of Luxembourg was the most important monarch in Europe in the 14th – 15th centuries. What is paradoxical is the presence of Stephan Lazarevic, son of Lazarus, Serbian tsar, martyr of European fame, as first knight in the Order of the Dragon. Lazarevic was a great patron of the Orthodox culture and civilization in Serbia. Lazarevic also owned a large palace with an Orthodox church, right in Buda. The Nemanide dynasty was the most important dynasty in forming an Orthodox monarchical idea in the Balkan area. Therefore, this study aims to highlight briefly the European history concerning the idea of unity of powers in a medieval society, the evolution of this idea in a troubled Europe, and especially in a Hungary insufficient Westerner or Byzantine, seeker of an ethnic and social ideal, which would become so specific to the Serbian people.